Труднощі перекладу науково-технічних англомовних текстів - Пашаєв Кенан Мамед огли (ХНУРЕ, 2019)
The article regards a number of peculiarities of translating scientific and technical texts. The author dwells upon the possible issues that a translator may stumble upon while translating a scientific document. The paper also analyzes and highlights the examples of possible inconsistencies that can cause inaccuracies of terms used in the text.